ECONOMIC CRISIS AND POLANYI'S DOUBLE MOVEMENT - ÜŞENMEZ, ÖZGÜR (CENTRAL BOHEMIA UNIV, 2016)
As experts discuss the causes and results of the 2008 financial crisis and ensuing Great Recession, economists of various strands, led mainly by Keynesians, are slowly beginning to question the supposed wisdom of unfettered markets. Since Keynesian-liberal disputes revolve around the symptoms of the crisis, rather than the historical and structural features of market economies, we consider a fresh approach about Polanyi's ideas on market, and his concept of double movement in regards to the effects of neo-liberalism on societies, as a timely intervention to these debates.
Keywords: Keynesian; Liberal; Polanyi; Double Movement